THE FORMATION OF JAPANESE AND U.S. EQUITY JOINT VENTURES IN CHINA - Pan, Yigang (Strategic Management Journal, 1997)
This study examines the characteristics of Japanese and U.S. equity joint ventures (EJVs) in China over a 15-year period. These EJVs were announced between 1979 and the end of 1993. Substantial differences are found with respect to six key characteristics. They are: selection of the Chinese partner, selection of the second foreign partner (when more than one foreign partner is involved), foreign equity ownership, foreign capital contribution, EJV business scope, and the EJV location. Tentative explanations for these differences are offered from the perspectives of risk orientation, cultural similarities, and the impact of political events in China. © 1997 by John Wiley & Sons, Ltd.